Hubungan Antara Persepsi Terhadap Insentif Dengan Intensi Turnover Karyawan - Purnomo, Astika Rangga Dwi, Drs. Muh. Amir, M.Si (2015)
The existence of distrust of employees against the Company, where performance is NOT too aware of. PERFORMANCE employees received less attention from the financial aspect. Whereas WITH EVERY company employees Thought Requires advanced and boarding costs are Good for review Progress Company. Purpose Of Research husband is to review determine: 1) To determine the relationship between incentive Against PERCEPTION WITH employee turnover intention; 2) To find out how big Impact Against incentive PERCEPTION WITH employee turnover intention; 3) To determine the level of employee incentive Against PERCEPTION; 4) To determine the level of employee turnover intention. POPULATION From Research husband is Winda Sari Batik Company employees were 70 active employees. Period Based on the research institute, using the whole POPULATION POPULATION. The necessary data through questionnaires PERCEPTION OF TIN Against incentives and turnover intention karyawan.Teknik The analysis of the data used is the analysis of current products, which previously carried the assumption of normality and linearity test. Results Of Research Husband is: 1) Both variables showed a significant negative correlation between perceptions of incentives WITH turnoverkaryawan intention, with the amount of value Correlation Coefficient -0382, p = 0.001 (p <0.01); 2) The amount of the incentive Against Impact PERCEPTION WITH employee turnover intention is 14.6% because there are still 85.4% The influence turnover intentions. For example: NOT feel appreciated, Compensation Yang NOT Enough, Enough NOT feel Break Time, change management, machines and office equipment Yang Outdated, unrealistic targets, Less Support (Ramadhyaz, 2012); 3) Perception on the subject of classified employee incentive ON High; and 4) the employee turnover intention ON subjects classified as Low.